2008
DOI: 10.1177/1076029608319946
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Prothrombotic Mutations on Factor Consumption in Adult Patients with Severe Hemophilia

Abstract: About 10% of patients with severe hemophilia exhibit a milder clinical phenotype with less frequent bleeds. Among many other factors, coinheritance of prothrombotic mutations have been proposed to act as modulators of clinical severity in severe hemophilia. We conducted a study to evaluate the impact of 3 prothrombotic mutations (factor V Leiden, factor II, and methylenetetrahydrofolate reductase mutations) on clinical phenotype of patients with severe hemophilia in our institution. For this purpose we compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
(14 reference statements)
0
9
0
1
Order By: Relevance
“…Several retrospective studies have looked at the effect of coinheritance of prothrombotic mutations, with contradictory results. 6,9,[14][15][16][17][18][19][20][21][22][23][24][25] Some studies have found that severe hemophiliacs carrying a prothrombotic mutation have a milder phenotype characterized by older age at diagnosis, 25 older age at first bleed, 15,17,26 lower annual bleeding frequency, and less arthropathy. 21,22 In contrast, other studies failed to find significant differences in severity of disease attributable to the presence of a prothrombotic mutation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several retrospective studies have looked at the effect of coinheritance of prothrombotic mutations, with contradictory results. 6,9,[14][15][16][17][18][19][20][21][22][23][24][25] Some studies have found that severe hemophiliacs carrying a prothrombotic mutation have a milder phenotype characterized by older age at diagnosis, 25 older age at first bleed, 15,17,26 lower annual bleeding frequency, and less arthropathy. 21,22 In contrast, other studies failed to find significant differences in severity of disease attributable to the presence of a prothrombotic mutation.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 In contrast, other studies failed to find significant differences in severity of disease attributable to the presence of a prothrombotic mutation. 6,14,23,24 These conflicting results, together with the low prevalence of inherited prothrombotic mutations in hemophiliacs, is such that it is unlikely that such prothrombotic risk factors will account for much of the heterogeneity in disease severity seen in patients with hemophilia.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast with these observations, several other groups did not observe a decrease in bleeding frequency in severe hemophiliacs carrying the factor V Leiden. [30][31][32][33][34][35][36][37][38] Arbini and colleagues 30 evaluated 21 patients with severe hemophilia A or B and a milder clinical phenotype and found that only one patient (with hemophilia B) was a carrier of the factor V Leiden mutation. Similarly, Arruda and colleagues 32 found that 3 of 113 patients with hemophilia of different severity had coinherited the factor V Leiden mutation, but the researchers did not detect any difference in the frequency of bleeding episodes or response to therapy between patients who did or did not have the mutation.…”
Section: Inherited Thrombophilia and Severe Congenital Hemophiliamentioning
confidence: 99%
“…The MTHFR 677TT genotype was previously reported to slightly improve the clinical phenotype in severe hemophilia A patients [42][43][44][45]. In 2009 Ar et al described a lower annual factor concentrate consumption in hemophilia A and B patients who carried a prothrombotic mutation -either factor V Leiden, factor II or a MTHFR genetic variant [46]. However, the difference was not statistically significant (p=0.203).…”
Section: Discussionmentioning
confidence: 99%